Resiliência e Processos Protetivos de Adolescentes com Deficiência Física e Surdez Incluídos em Escolas Regulares - Libório, Renata Maria Coimbra; Castro, Bernardo Monteiro De; Ferro, Elaine Gomes; Souza, Marilza Terezinha Soares (Associação Brasileira de Pesquisadores em Educação Especial - ABPEE, 2015)
The paper presents the results of a survey conducted in two medium sized cities in the state of São Paulo, aimeing to identify and analyze protective processes associated with resilience. The participants were 16 teenagers, aged 14 to 17 years, who were exposed to adversities. This paper presents the results related to 4 adolescents with physical disabilities or deafness who are included in regular schools. An exploratory study was carried out, using semi-structured interviews and visual methods (photographs and videotaped recordings of daily life), which were analyzed according to Grounded Theory. Several aspects were identified regarding: 1) the participants' resilience processes associated to the quality of interpersonal relationships established among themselves, their peers and education professionals, underscoring the teacher interpreters; 2) the use of technology and social media in fostering communication between these students, their friends and family members without disabilities, and 3) the use of coping strategies to deal with pain and physical limitations, aiming for medium term well-being. The paper highlights the importance of working towards promoting a strengthening process for young people with disabilities in order to provide them with a pathway towards educational and social inclusion through reflections on the role played by schools in their lives, so as to promote resilience processes.

O artigo apresenta os resultados de uma pesquisa, realizada em duas cidades de médio porte do estado de São Paulo, cujo objetivo foi identificar e analisar processos protetivos associados à resiliência. Os participantes foram 16 adolescentes, de faixa etária entre 14 e 17 anos, expostos a adversidades. Neste trabalho são apresentados os resultados referentes a quatro adolescentes com deficiência física ou auditiva incluídos em escolas regulares. Foi realizado um estudo exploratório, incluindo entrevistas semiestruturadas e métodos visuais (fotografias e filmagens do cotidiano), os quais foram analisados segundo a Teoria Fundamentada nos Dados (TFD). Foram identificados diversos aspectos relativos: 1) aos processos de resiliência dos participantes, associados à qualidade dos relacionamentos interpessoais estabelecidos entre eles, colegas e profissionais da educação, com destaque para os professores intérpretes; 2) ao uso das tecnologias e mídias sociais no favorecimento da comunicação entre eles, amigos e familiares sem deficiência, e 2) às estratégias de enfrentamento da dor e das limitações físicas visando ao bem-estar a médio prazo. Ressalta-se a necessidade de trabalhar em prol do fortalecimento dos adolescentes com deficiência e de auxiliá-los na promoção de seu caminho em direção à inclusão escolar e social, por meio de reflexões sobre o lugar ocupado pelas escolas em suas vidas, o que pode favorecer os processos de resiliência.
Resilience and Protective Processes of Adolescents with Physical Disabilities and Deafness Included in Regular Schools
Keywords: Special Education; Resilience; Deafness; Physical Disability; School Inclusion; Educação Especial; Resiliência; Surdez; Deficiência física; Inclusão Escolar